Tratamento preventivo da raiva humana Preventive treatment against rabies in humans - Murillo Pacca de Azevedo; Pedro José Barbante; Sosthenes Vital Kerbrie; Marcia Caraça Cortás (Universidade de São Paulo, 1981)
Foi elaborada Norma Técnica por uma Comissão constituída pelo Serviço Especial de Saúde Pública do Ministério da Saúde com a participação de represeentantes de vários estados brasileiros para que seja adotado, em todo o território nacional, um mesmo esquema de tratamento anti-rábico preventivo humano pós-exposição ao contágio. A technical note has been elaborated by a working-group coordinated by the "Serviço Especial de Saúde Pública" of the "Ministério da Saúde" with the participation of experts from various Brazilian States with a view to the adaptation, throughout Brazil, of the same technical norms for post-exposure anti-rabies preventive treatment.